Distribution and partitioning of major and trace elements in pyrite-bearing sediments of a Mediterranean coastal lagoon - Botsou, F; Godelitsas, A.; Kaberi, H.; Mertzimekis, T. J.; J. Goettlicher; R. Steininger; M. Scoullos (Chemie der Erde, 2015)
Abstract The formation of iron sulphide minerals exerts significant control on the behaviour of trace elements in sediments. In this study, three short sediment cores, retrieved from the remote Antinioti lagoon (N. Kerkyra Island, \{NW\} Greece), are investigated concerning the solid phase composition, distribution, and partitioning of major (Al, Fe) and trace elements (Cd, Cu, Mn, Pb, and Zn). According to $^{210}$Pb, the sediments sampled correspond to depositions of the last 120 years. The high amounts of organic carbon (4.1–27.5%) result in the formation of Fe sulphides, predominantly pyrite, already at the surface sediment layers. Pyrite morphologies include monocrystals, polyframboids, and complex FeS–FeS$_2$ aggregates. According to synchrotron-generated micro X-ray fluorescence and X-ray absorption near-edge structure spectra, authigenically formed, Mn-containing, Fe(III) oxyhydroxides (goethite type) co-exist with pyrite in the sediments studied. Microscopic techniques evidence the formation of galena, sphalerite and CuS, whereas sequential extractions show that carbonates are important hosts for Mn, Cd, and Zn. However, significant percentages of non-lattice held elements are bound to Fe/Mn oxyhydroxides that resist reductive dissolution (on average 60% of Pb, 46% of Cd, 43% of Zn and 9% of Cu). The partitioning pattern changes drastically in the deeper part of the core that is influenced by freshwater inputs. In these sediments, the post-depositional pyritization mechanism, illustrated by overgrowths of Fe monosulphides on pre-existing pyrite grains, results in relatively high degree of pyritization that reaches 49% for Cd, 66% for Cu, 32% for Zn and 7% for Pb.
Keywords: Lagoon sediments